Working status is not related to exclusive breastfeeding - Agung Nugroho (Universitas 'Aisyiyah Yogyakarta, 2022)
Breast Milk is known as the best food for babies and contains many nutritious substances. Many factors influenced successful breastfeeding, especially for working mothers. This study is intended to explore the relationship between mothers' employment status and breastfeeding status using a cross-sectional design that utilizes secondary data collected from the implementation of the